Uncovering the shared molecule and mechanism between ulcerative colitis and atherosclerosis: an integrative genomic analysis - Huang, Jinke; Wang, Fengyun; Tang, Xudong (Frontiers in Immunology, 2023)
Background: Ulcerative colitis (UC) and atherosclerosis (AS) are closely related. However, the pathologic mechanisms underlying the co-occurrence of UC and AS are not well understood. Objects: To reveal the hub molecule and mechanism involved in the co-occurrence of UC and AS. Methods: Differentially expressed genes (DEGs) of UC and AS were obtained and the shared DEGs of UC and AS were explored for biological function. Next, the hub gene was explored using the cytoHubba plugin. Predictive ability of the hub gene was measured by constructing receiver operating characteristic curve. Analyses of immune infiltration and the single-gene GSEA analysis for the hub gene were further carried out. Results: Identification of 59 DEGs (55 were upregulated and 4 were downregulated) shared by both UC and AS. Enriched pathways of the shared DEGs mainly related to immunity and inflammation. Protein tyrosine phosphatase, receptor type, C (PTPRC) was identified as the hub crosstalk gene for the co-morbidity of UC and AS. The upregulation of PTPRC was correlated with mast cells resting, T cells CD4 memory resting, macrophages M0, and macrophages M1. Pathways of immune and inflammatory processes, including NF-kappa B, viral protein interaction with cytokine and cytokine receptor, and cytokine-cytokine receptor interaction were significantly correlated with high expression of PTPRC in UC and AS. Conclusions: At the transcriptional level, our study reveals that imbalanced inflammatory and immune responses are the key pathological mechanisms underlying the co-morbidity of UC and AS, and that PTPRC is a key biomarker for the co-morbidity of UC and AS.